DEVELOPMENT OF A REFERENCE BOOK BASED ON THE IDENTIFICATION DATA OF MEDICINAL PLANTS IN THE COMMUNITY OF THE SULTANATE OF MOLOKU KIERAHA, NORTH MALUKU, INDONESIA - Haerullah, Ade; Hasan, Said; Sahil, Jailan (International Journal of Social Service and Research, 2024)
The aim of this research is to develop teaching materials in the form of a reference book based on studies of plant medicinal identification in the people of the Moloku Kieraha sultanate. The research involved students in semester 2 of the Unkhair Postgraduate Biology Education program for the 2023/2024 academic year. The study used interview sheets, observation sheets, validation sheets, and response questionnaires for data collection, and validation sheet and product trial analysis for analysis. The results of the research identifies 36 medicinal plants used by the Serawai tribe community in Torano Village, Central Ternate District, Maluku Province. Phytochemical analysis reveals that these plants contain secondary metabolite compounds, including tannins, alkaloids, saponins, flavonoids, terpenoids, and steroids. Students showed a positive response to the medicinal plant reference book that had been developed, with an interest level reaching 98%. Therefore, teaching materials are needed to guide students in conducting phytochemical tests to determine the content, benefits, and techniques of phytochemical screening in natural materials.